2010
DOI: 10.4269/ajtmh.2010.09-0434
|View full text |Cite
|
Sign up to set email alerts
|

Autochthonous Visceral Leishmaniasis in a Human Immunodeficiency Virus (HIV)-Infected Patient: The First in Thailand and Review of the Literature

Abstract: Abstract. We report a case of visceral leishmaniasis in a human immunodeficiency virus (HIV)-infected 37-year-old Thai fisherman who presented with nephritonephrotic syndrome, fever, anemia, and thrombocytopenia. Bone marrow biopsy revealed many amastigotes within macrophages. Kidney biopsy showed membranoproliferative glomerulonephritis. Polymerase chain reaction (PCR) and nucleotide sequence analysis of the internal transcribed spacer 1 of the small subunit ribosomal RNA gene in blood and kidney biopsy speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
54
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 13 publications
0
54
0
1
Order By: Relevance
“…The phylogenetic tree showed that the L. martiniquensis reference sequence was grouped with the same taxa that have been identified as L. siamensis suggesting that most isolates would belong to L. martiniquensis. Figure 2 includes the Leishmania sequences obtained from sandflies and black rats in the study of animal reservoirs and potential vectors of L. siamensis by Chusri and others (JQ866907, JQ866906) 25 and sequences belong to L. siamensis lineage PG previously isolated from Thai patients (GQ226034, GQ293226, JQ001751, and JQ001752), 10,18,19 horses (JQ617283, GQ281278, GQ281279, GQ281280, and GQ281281), 16,21 and cows (GQ281282). 17 However, the L. siamensis lineage TR, ∥The sequences of accession number JQ001752 and KF227887 to KF227892 were obtained from the specimens collected from the same source but different site of specimen collection.…”
Section: Phylogenetic Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The phylogenetic tree showed that the L. martiniquensis reference sequence was grouped with the same taxa that have been identified as L. siamensis suggesting that most isolates would belong to L. martiniquensis. Figure 2 includes the Leishmania sequences obtained from sandflies and black rats in the study of animal reservoirs and potential vectors of L. siamensis by Chusri and others (JQ866907, JQ866906) 25 and sequences belong to L. siamensis lineage PG previously isolated from Thai patients (GQ226034, GQ293226, JQ001751, and JQ001752), 10,18,19 horses (JQ617283, GQ281278, GQ281279, GQ281280, and GQ281281), 16,21 and cows (GQ281282). 17 However, the L. siamensis lineage TR, ∥The sequences of accession number JQ001752 and KF227887 to KF227892 were obtained from the specimens collected from the same source but different site of specimen collection.…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…Phang-nga, 15 4. Chanthaburi, 18 15 The map of Thailand shows sporadic cases of CL and VL reported in six southern, one central, one eastern, and four northern provinces. Table 3 shows the characteristics of published leishmaniasis cases in Thailand from 1999 to 2016.…”
Section: Situation Of Leishmaniasis In Thailandmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7] In comparisons of microscopic examination, culture, and PCR in detecting Leishmania parasites, PCR has shown to have a significantly higher sensitivity than culture and microscopic examination (97%, 78%, and 76% [8][9][10] sensitivity, respectively). New cases of leishmaniasis caused by L. siamensis, a novel species of Leishmania, have been documented in patients in Thailand [11][12][13][14][15][16][17] and Myanmar (unpublished data). The infection was described in immunocompromised patients, mostly persons infected with human immunodeficiency virus (HIV).…”
mentioning
confidence: 99%
“…The infection was described in immunocompromised patients, mostly persons infected with human immunodeficiency virus (HIV). [11][12][13][14][15][16][17] Clinical presentations of these patients have included visceral, [11][12][13] diffuse cutaneous, 15 and overlapping diffuse cutaneous and visceral forms. 14 With low prevalence of leishmaniasis in Thailand and Myanmar, screening tests for leishmaniasis such as enzymelinked immunosorbent assay, direct agglutination test, and recombinant protein K39 dipstick test are not readily available.…”
mentioning
confidence: 99%